Dynamic simulations for preparing the acceptance test of JT-60SA cryogenic system. (December 2016) - Cirillo, R.; Hoa, C.; Michel, F.; Poncet, J.M.; Rousset, B.
Highlights: EcosimPro can be used to model JT-60SA ACB. The isochoric operation for JT-60SA ACB has been modelled and analyzed. A new "mass control strategy" has been assessed for the liquid helium bath. Abstract: Power generation in the future could be provided by thermo-nuclear fusion reactors like tokamaks. There inside, the fusion reaction takes place thanks to the generation of plasmas at hundreds of millions of degrees that must be confined magnetically with superconductive coils, cooled down to around 4.5 K. Within this frame, an experimental tokamak device, JT-60SA is currently under construction in Naka (Japan). The plasma works cyclically and the coil system is subject to pulsed heat loads. In order to size the refrigerator close to the average power and hence optimizing investment and operational costs, measures have to be taken to smooth the heat load. Here we present a dynamic model of the JT-60SA's Auxiliary Cold box (ACB) for preparing the acceptance tests of the refrigeration system planned in 2016 in Naka. The aim of this study is to simulate the pulsed load scenarios using different process controls. All the simulations have been performed with EcosimPro® and the associated cryogenic library: CRYOLIB.